The Electronic Diaries (1984-1996) di Lynn Hershman Leeson - Roaro, Eleonora (Scenari, 2021)
his essay focuses on Lynn Hershman Leesons (Cleveland, 1941 – known as Lynn Hershman until 1992), in particular on her project The Electronic Diaries (1986-1998) in which she uses the video-camera not only as a medium of confession and control, but also for the construction of gender and identity. On purpose, a stereotyped version of the feminine emerges from what she reveals about herself, as her main topics are the divorce from her husband and the acceptance of her body. In this way Lynn Hershman Leeson demonstrates that gender does not exist a priori, but is socially, historically and technologically constructed. The relationship between technology and subjectivity is analyzed with references to video-art according to Rosalind Krauss, Yvonne Spielmann, Ina Blom and Micki McGee: the characteristics of the medium itself, particularly its immediacy, make it the perfect instrument for auto-biography and confession. Another important concept for her research is the cyborg which, according to Donna Haraway, is conceived as a cybernetic organism that exceeds the dualisms on which western culture is based: male/female, culture/nature, mind/body.